2021
DOI: 10.33448/rsd-v10i1.11471
|View full text |Cite
|
Sign up to set email alerts
|

Associações entre prática de atividade física e qualidade do sono no contexto pandêmico de distanciamento social

Abstract: Este estudo teve como objetivo investigar possíveis associações entre prática de atividade física e qualidade do sono durante o período de distanciamento social da pandemia de COVID-19. Participaram 458 adultos com idades entre 18 e 59 anos. O nível de atividade física foi investigado por meio do Questionário Internacional de Atividade Física (IPAQ) e a qualidade do sono pelo Mini Sleep Questionnaire (MSQ). Os resultados demonstraram que 79,3% dos participantes com algum nível de dificuldade do sono. A prática… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
2
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 29 publications
3
2
0
5
Order By: Relevance
“…While during the period of social isolation, Da Silva et al (2021) showed that physical inactivity increased 26% in the national territory (Da Silva et al, 2021). Our findings are similar to those of Cavalcante et al (2021), who investigated Brazilian adults through an online questionnaire in 2020. The results showed that the higher physical activity group presented a better sleep quality, compared to those active and insufficiently active (Cavalcante et al, 2021).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…While during the period of social isolation, Da Silva et al (2021) showed that physical inactivity increased 26% in the national territory (Da Silva et al, 2021). Our findings are similar to those of Cavalcante et al (2021), who investigated Brazilian adults through an online questionnaire in 2020. The results showed that the higher physical activity group presented a better sleep quality, compared to those active and insufficiently active (Cavalcante et al, 2021).…”
Section: Discussionsupporting
confidence: 92%
“…Our findings are similar to those of Cavalcante et al (2021), who investigated Brazilian adults through an online questionnaire in 2020. The results showed that the higher physical activity group presented a better sleep quality, compared to those active and insufficiently active (Cavalcante et al, 2021).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Assim também, uma alimentação balanceada fortalece o organismo a se manter em equilíbrio, físico, psíquico e imunológico, agregando melhores condições para vida em isolamento social. 41,42 Outras manifestações de natureza diversas também foram identificadas. Mas destaca-se os problemas de ordem financeira, e familiares.…”
Section: Materiais E Métodosunclassified
“…The health benefits of PA may be even more important during the Coronavirus pandemic (COVID-19) since many people have experienced mental health problems related to social isolation (RODRÍGUEZ-REY; GARRIDO-HERNANSAIZ; COLLADO, 2020). The practice of PA during the pandemic, including LTPA, has been associated with several benefits for individuals (CAVALCANTE et al, 2021;SCHUCH et al, 2020;TESTA et al, 2021). In Brazil, for instance, Schuch et al (2020) observed that individuals who underwent ≥ 30 minutes/day of moderate to vigorous PA or ≥ 15 minutes/day of vigorous PA were less likely to report depressive symptoms and anxiety.…”
Section: Introductionmentioning
confidence: 99%